ANALISIS KEBERLANJUTAN SUMBERDAYA PERIKANAN DENGAN MENGGUNAKAN JARING PERANGKAP (TRAP NET) DI WILAYAH PESISIR PANTAI KABUPATEN PANGKEP - Risnawati Bahtiar; Syahrul Djafar; Ihsan Ihsan (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2019)
Research of the sustainability analysis of fisheries resources by using trap net in the coastal of Pangkep Regency was conducted on August to October 2018 in the coastal zone of pangkep Regency. This research aims to 1) Analyze the location of trap net fishing areas, (2) Analyze environmental friendliness of trap net, (3) Analyze the sustainability of fish resources by using trap net in the coastal areas of Pangkep district. The method used was case study by following fishing operations using trap net directly. Analyzed of the determination of the trap net installation location was used by geographic information systems (GIS), analyzed the selectivity of fishing gear used the formula based on the provisions of FAO (1995), and analyzed the sustainability of fish resources used Rapfish analysis. Results of the research showed that fishing ground of using trap net covers the coastal areas of Pangkep Regency, there were four locations that have been determined based on analysis, which were Districts of Bungoro, Labakkang, Ma'rang, and Segeri. Trap net included in fishing gear that was not environmentally friendly, so it does not support the sustainability of fisheries resources. Utilization of fishery resources by using a trap net in the coastal areas of Pangkep Regency is less sustainable.